2020
DOI: 10.3390/agronomy10020219
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diseases in Two North-West Spain Vineyards: Relationship with Meteorological Conditions and Predictive Aerobiological Model

Abstract: Grey mould, powdery mildew, and downy mildew are the most frequent fungal diseases among vineyards worldwide. In the present study, we analysed the influence of the fungi causing these diseases (Botrytis, Erysiphe, and Plasmopara, respectively) on two viticulture areas from North-western (NW) Spain during three growth seasons (2016, 2017, and 2018). The obtained results showed the predominant concentration of the Botrytis airborne spores, mainly from the beginning of the Inflorescence emerge phenological stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…Concerning airborne P. viticola sporangia, the current study confirmed other reports that P. viticola sporangia are a common component of the airborne microflora of vineyards (Diaz et al, 1998;Albelda et al, 2005;Fernandez-Gonzalez et al, 2009;Magyar et al, 2009;Fernández-González et al, 2011Martínez-Bracero et al, 2019;Rodríguez et al, 2020). This is highly relevant to DM management: while the inoculum for primary infection is available only following a rain, the secondary inoculum is always present when P. viticola is established in the vineyard.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Concerning airborne P. viticola sporangia, the current study confirmed other reports that P. viticola sporangia are a common component of the airborne microflora of vineyards (Diaz et al, 1998;Albelda et al, 2005;Fernandez-Gonzalez et al, 2009;Magyar et al, 2009;Fernández-González et al, 2011Martínez-Bracero et al, 2019;Rodríguez et al, 2020). This is highly relevant to DM management: while the inoculum for primary infection is available only following a rain, the secondary inoculum is always present when P. viticola is established in the vineyard.…”
Section: Discussionsupporting
confidence: 89%
“…The next model step consists of DM-free sites on which the sporangia deposit after being detached from sporangiophores on sporulating DM lesions and dispersed into the air (Figure 1). Because P. viticola sporangia become airborne under a wide range of environmental conditions (Caffi et al, 2013a) and because they are normally present in the air of DM-affected vineyards (Diaz et al, 1997(Diaz et al, , 1998Albelda et al, 2005;Fernandez-Gonzalez et al, 2009;Magyar et al, 2009;Fernández-González et al, 2011Martínez-Bracero et al, 2019;Rodríguez et al, 2020), the model assumes that whenever there are sporangia on DM lesions, sporangia may detach, disperse, and be deposited on the host surface, i.e., when D' > 0; if D' = 0, there are no viable sporangia, and the model run ends.…”
Section: Spore Dispersal and Deposition Compartmentmentioning
confidence: 99%
“…Largely, the spore concentrations showed a positive correlation with temperatures and relative humidity and negative relation with rainfall and wind speed. The similar behavior has been pointed out by several author in other environments, such as for Aspergillus/Penicillium airborne spores [70] or other phytopathogen spores such as Botrytis, Erysiphe or Plasmopara in Vitis vinifera crops [76].…”
Section: Discussionsupporting
confidence: 83%
“…The alternative to the exclusive use of synthetic chemical plant protection in the fight against powdery mildew should be focused on three areas: preventive agronomic treatments, biological control and chemical fungicides used rationally (Cortiñas et al 2020).…”
Section: Alternatives For a More Sustainable Control Of Phytosanitary Products In Ribeira Sacramentioning
confidence: 99%